The Role of Servant Leadership in Developing Spiritual Formation of Teachers - Ruata, Gloria Solideo; Tung, Khoe Yao (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
Leadership is the ability of an individual who holds a position and capacity to lead. Logically, a leader who leads must have others to lead and/or who will be led. Leadership can be examined from two aspects, namely religious/spiritual leadership and secular/natural leadership. The leadership to be addressed in this research is Christian Leadership with an emphasis on Servant Leadership. The aim of this research is to explore the phenomenon of Servant Leadership and explain its impact on spiritual growth. In this case, the role of Servant Leadership to be explored is the Servant Leadership of the Principal of SMP Dian Harapan Holland Village Manado, and its impact on the spiritual growth of fresh graduate teachers as individuals or followers who are led, based on a case study conducted on an object and subject of research. The research method used is qualitative with a case study approach. From the results of this research, it was found that fresh graduate teachers with less than one year of teaching experience can see, experience, and feel the Servant Leadership of the Principal of SMP Dian Harapan Holland Village Manado, which is considered as a humble person, through relationships, interactions, and communication with the Principal. The role of the Servant Leadership of the Principal is also perceived by fresh graduate teachers as helpful in their spiritual formation through mentoring, encouragement, and spiritual activities at school.